Severe respiratory insufficiency in chest trauma - Tamborindeguy, Luis (Cirugía del Uruguay, 1990)
Acute Respiratory Failure (I.R.A.) is the disability of the lung to fulfill its respiratory function gas exchange and is characterized pathophysiologically due to severe hypoxemia with or without hypercapnia.